Myxomycetes diversity in Adana Province (Turkey) with two new records - Baba, Hayri̇; Sevi̇ndi̇k, Mustafa (Phytotaxa, 2022)
Samples were collected in Adana province during 2019–2021 and myxomycetes were cultured using the moist chamber technique. The samples consisted of rotten or live tree bark, leaves, rashes, vegetable, and animal material, which were considered likely to contain myxomycete spores. In adddition, natural myxomycete samples were collected at nine different stations. These ‘natural samples’ were immediately dried and potential spore-bearing material was kept in a warm and humid environment with the moist chamber technique. In total, 56 myxomycetes (205 samples; 148 by moist chamber technique and 57 ‘natural samples’) were obtained representing six orders, 12 families, 24 genera and 56 species. Eight species were collected only in natural samples, 35 species were obtained only by moist chamber technique in the laboratory, and 13 species were obtained by both methods. Two myxomycetes as new records (Licea rugosa and Physarum nivale) and one new locality (Cribraria lepida) were identified in Turkey